Molecular Changes and Their Ratio in Preeclamptic Patients - S, Khatun; AKA, Mahmood; SF, Afrin; S, Jahan; MK, Nishi; U, Salma (Bangladesh Journal of Medical Science, 2025)
Background Preeclampsia is a leading cause of maternal and fetal morbidity and mortality. Although its exact etiology remains unclear, alterations in serum uric acid and creatinine levels are thought to be associated with the condition. Objective This study was aimed to evaluate serum uric acid and creatinine levels and their ratio in preeclamptic women for early diagnosis and prevent the complications by using these easy biochemical lab parameters. Methods A cross-sectional study was conducted in the Department of Biochemistry, Mymensingh Medical College, in collaboration with the Department of Obstetrics and Gynecology, Mymensingh Medical College & Hospital. A total of 120 pregnant women were selected through purposive (non-random) sampling based on specific inclusion and exclusion criteria. Of these, 60 were diagnosed with preeclampsia (cases), and 60 normotensive pregnant women served as controls. Serum levels of uric acid, and creatinine were measured and expressed as mean ± standard deviation (SD), and the ratio of SUA/Scr is analyzed by logistics regression analysis. Data were analyzed using SPSS version 21, and differences between groups were assessed using Student’s unpaired t-test. Results The analysis revealed a highly significant increase (P < 0.001) in serum uric acid and creatinine levels in preeclamptic patients compared to controls.The ratio of SUA/Scr also higher as compare to control. Conclusion The study demonstrates that serum uric acid and creatinine levels and their ratio are significantly elevated in preeclamptic women, suggesting their potential role in the pathophysiology and management of preeclampsia. BJMS, Vol. 24 No. 03 July’25 Page : 916-922